A Novel Hybrid Secure Routing for Flying Ad-hoc Networks - Raj, Jennifer S. (Journal of Trends in Computer Science and Smart Technology, 2020)
• The recent technology development increases the opportunity to create valuable network services to user. Flying ad-hoc networks (FANET) in one among them which evolved recently with enhanced value added services with common features similar to its predecessor ad-hoc networks like vehicular ad hoc networks (VANET) and mobile ad hoc networks (MANET). Due to its distinctive features FANETs are widely preferred in recent telecommunication services which requires high quality of services, efficiency, environment adaptability and scalability. In order to achieve high efficiency multiple aerial vehicles are used in general architectures. The Communication in such vehicles are progressed directly between the nodes or through relay nodes. Routing is an important process to establish a connection link between the nodes in the architecture. This research work proposed a routing strategy suitable for dynamic and static environments as a hybrid optimization model which reduces the issues in link establishment. Nature inspired bee colony optimization is used along with conventional routing algorithms such as optimized link state routing protocol and Dynamic Source Routing Protocol to improve the link discovery. The proposed optimized routing outperforms well in reduced delay and communication overhead of the network.